THE WAYS OF TRANSLATING IDIOMS FROM ENGLISH INTO UZBEK - Soliyev, Abrorjon; Nabiyeva, Mahliyo (Educational Research in Universal Sciences, 2023)
This article highlights the ways of translating English idioms into Uzbek. Here are given some examples of vegetable idioms in English and their translations into Uzbek is analyzed.